2024
DOI: 10.1186/s12933-024-02208-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperlipidemia and body fat distribution on subclinical left ventricular function in obesity: a cardiovascular magnetic resonance study

Jing Liu,
Jing Li,
Chunchao Xia
et al.

Abstract: Background Obesity is often associated with multiple comorbidities. However, whether obese subjects with hyperlipidemia in the absence of other complications have worse cardiac indices than metabolically healthy obese subjects is unclear. Therefore, we aimed to determine the effect of hyperlipidemia on subclinical left ventricular (LV) function in obesity and to evaluate the association of cardiac parameters with body fat distribution. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Body fat distribution was assessed by DXA (Lunar iDXA, GE Medical Systems Lunar, Madison, WI, USA). The specific region of interest of fat deposit regions was displayed in a previous study ( 12 ). The percentage of fat mass in visceral, trunk, upper and lower extremities, android, and gynoid areas was calculated by dividing fat mass in the corresponding regions by total fat mass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body fat distribution was assessed by DXA (Lunar iDXA, GE Medical Systems Lunar, Madison, WI, USA). The specific region of interest of fat deposit regions was displayed in a previous study ( 12 ). The percentage of fat mass in visceral, trunk, upper and lower extremities, android, and gynoid areas was calculated by dividing fat mass in the corresponding regions by total fat mass.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that fat deposition of different regions (such as visceral or subcutaneous adipose tissue) had distinct effects on heart. Dual X-ray absorptiometry (DXA) further divides body fat, such as fat deposits in arms and legs, trunk, android, gynoid, or visceral regions ( 12 ). These fat tissues have been linked to cardiovascular risk factors ( 13 - 15 ); however, the effect of fat distribution in these regional areas on left heart function is not clear yet.…”
Section: Introductionmentioning
confidence: 99%